2008
DOI: 10.1016/j.neuron.2008.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Dynamics in Dendritic Microdomains

Abstract: Among diverse factors regulating excitatory synaptic transmission, the abundance of postsynaptic glutamate receptors figures prominently in molecular memory and learning-related synaptic plasticity. To allow for both long-term maintenance of synaptic transmission and acute changes in synaptic strength, the relative rates of glutamate receptor insertion and removal must be tightly regulated. Interactions with scaffolding proteins control the targeting and signaling properties of glutamate receptors within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
279
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(291 citation statements)
references
References 309 publications
(516 reference statements)
8
279
0
4
Order By: Relevance
“…These perisynaptic AMPARs can be removed by moderate synaptic activity (10) and this removal prevents the full expression of LTP and reverses spine expansion (6, 10). It has been suggested that perisynaptic AMPARs could play a critical role in regulating the persistence of LTP and spine expansion (10,12). This notion is consistent with the observation that stabilization of spine expansion requires synaptic incorporation of new AMPARs (6, 13).…”
supporting
confidence: 77%
“…These perisynaptic AMPARs can be removed by moderate synaptic activity (10) and this removal prevents the full expression of LTP and reverses spine expansion (6, 10). It has been suggested that perisynaptic AMPARs could play a critical role in regulating the persistence of LTP and spine expansion (10,12). This notion is consistent with the observation that stabilization of spine expansion requires synaptic incorporation of new AMPARs (6, 13).…”
supporting
confidence: 77%
“…There is now a large body of experimental evidence that the fast trafficking of AMPA receptors into and out of spines is a major contributor to activity-dependent, long-lasting changes in synaptic strength (Bredt and Nicoll, 2003;Collinridge et al, 2004;Henley et al, 2011;Shepherd and Huganir, 2007). Single-particle tracking experiments suggest that surface AMPA receptors diffuse freely within the dendritic membrane until they enter a spine, where they are temporarily confined by the geometry of the spine and through interactions with scaffolding proteins and cytoskeletal elements (Choquet and Triller, 2003;Ehlers et al, 2007;Gerrow and Triller, 2010;Groc et al, 2004;Newpher and Ehlers, 2008;Triller and Choquet, 2005). A surface receptor may also be internalized via endocytosis and stored within an intracellular pool, where it is either recycled to the surface via exocytosis or degraded (Ehlers, 2000), see Fig.…”
Section: Diffusion Along Spiny Dendritesmentioning
confidence: 99%
“…The challenges of intracellular transport are particularly acute for brain cells (neurons), which are amongst the largest and most complex cells in biology, in particular, with regards to the efficient trafficking of newly synthesized proteins from the cell body or soma to distant locations on the axon or dendrites. In healthy cells, the regulation of protein trafficking within a neuron provides an important mechanism for modifying the strength of synaptic connections between neurons (Bredt and Nicoll, 2003;Choquet and Triller, 2003;Newpher and Ehlers, 2008;Triller and Choquet, 2005), and synaptic plasticity is generally believed to be the cellular substrate of learning and memory. On the other hand, various types of dysfunction in protein trafficking appear to be a major contributory factor to a number of neurodegenerative diseases associated with memory loss including Alzheimers (de Vos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have characterized the alternative splicing changes in Gria2 and Gria4, which encode core subunits of AMPA-type glutamate receptors that are critical for glutamatergic excitatory synapses (39). Alternative splicing via mutually exclusive exons generates flip or flop isoforms affecting the ligand-binding domain, which imparts different pharmacologic and kinetic properties on currents evoked by L-glutamate or AMPA (40).…”
Section: Sma Primarily Affects Spinal Cord Mnsmentioning
confidence: 99%